2016
DOI: 10.3354/esr00720
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weather on a population of soprano pipistrelle bats in West Wales, UK: a 20 year study estimates population viability

Abstract: A nursery roost of the soprano pipstrelle bat Pipistrellus pygmaeus has been monitored continuously between 1 April and 27 September (Weeks 1−26) for 20 yr to promote conservation of the species, which declined over the last century. The long-term study, essential to estimate a reliable population trend, is linked to environmental changes as possible causes of decline. The main emergence was from May to July (Weeks 6−18) when 550 ± 190 (SD) P. pygmaeus were counted. Analysis showed that the year-to-year change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…During a simulated year, we multiplied each colony size with a growth rate selected from a normal distribution with an expected value of 1 and a standard deviation ( SD ) of either 0.1 or 0.01, which remained constant across years and colonies. The two standard deviations represent high and low temporal variability in colony size, respectively, and are consistent with bat population dynamics reported in the literature (Andrews, Crump, Harries, & Andrews, 2016; Chauvenet, Hutson, Smith, & Aegerter, 2014; Schaub, Gimenez, Sierro, & Arlettaz, 2007). We simulated roost abandonment by randomly selecting a given percentage of colonies which would abandon their roost at the end of a simulated year and establish a new roost.…”
Section: Methodssupporting
confidence: 87%
“…During a simulated year, we multiplied each colony size with a growth rate selected from a normal distribution with an expected value of 1 and a standard deviation ( SD ) of either 0.1 or 0.01, which remained constant across years and colonies. The two standard deviations represent high and low temporal variability in colony size, respectively, and are consistent with bat population dynamics reported in the literature (Andrews, Crump, Harries, & Andrews, 2016; Chauvenet, Hutson, Smith, & Aegerter, 2014; Schaub, Gimenez, Sierro, & Arlettaz, 2007). We simulated roost abandonment by randomly selecting a given percentage of colonies which would abandon their roost at the end of a simulated year and establish a new roost.…”
Section: Methodssupporting
confidence: 87%
“…Early spring corresponds to the most vulnerable period for bats as their energy reserves will be at their lowest following hibernation, and food availability is therefore critical. Thus, warm springs which cause both an increase in insect food supplies but also an extended feeding season for bats since prey becomes available earlier in the season may be highly favourable to the bats (but see Andrews et al 2016 who suggest that a delay in insect emergence may favour female pipistrelle bats in gestation/lactation). Considering the significant increase in spring temperatures in recent decades in the UK (Online Resource 8), there is strong support that climate warming has contributed to population growth.…”
Section: Landscape Characteristics Affect Colony Size At Different Spmentioning
confidence: 99%
“…Habitat preferences for P. pygmaeus are considered to be different than those of P. pipistrellus , with the former detected more frequently in riparian habitats and the latter detected in a wider variety of habitats, as also reported by Walsh and Harris (). This study has revealed that the Lledr valley is a potentially suitable foraging area for P. pygmaeus , which in Wales, may be at risk from climate change, since higher winter temperatures between January and March have been linked to previously a smaller population size (Andrews, Crump, Harries, & Andrews, ).…”
Section: Discussionmentioning
confidence: 94%